2020
DOI: 10.1159/000506703
|View full text |Cite
|
Sign up to set email alerts
|

How Often Are Patient-Important Outcomes Represented in Neonatal Randomized Controlled Trials? An Analysis of Cochrane Neonatal Reviews

Abstract: <b><i>Background:</i></b> Research findings based on patient-important outcomes (PIOs) provide more useful conclusions than those that are based on surrogate outcomes. It is unclear to what extent PIOs are represented in neonatal randomized controlled trials (RCTs). <b><i>Objectives:</i></b> We determined the proportion of PIOs in neonatal RCTs included in Cochrane Neonatal reviews. <b><i>Methods:</i></b> We extracted up to 5 outcomes from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…The findings in this study serve as an example of clinical research in which a surrogate outcome that is widely used in practice is favored over the outcomes that actually matter to the patients. They echo the finding of a previous study that assessed data from all Cochrane Neonatal reviews, which showed that 7.2% of all the RCTs included in Cochrane Neonatal reviews reported only surrogate outcomes without any PIO [29]. Although surrogate outcomes, like serum bilirubin, are popular in clinical research due to their relative ease of measurement, overreliance on them may result in misleading interpretation of trial results and inappropriate practice recommendations [30-32].…”
Section: Discussionsupporting
confidence: 53%
“…The findings in this study serve as an example of clinical research in which a surrogate outcome that is widely used in practice is favored over the outcomes that actually matter to the patients. They echo the finding of a previous study that assessed data from all Cochrane Neonatal reviews, which showed that 7.2% of all the RCTs included in Cochrane Neonatal reviews reported only surrogate outcomes without any PIO [29]. Although surrogate outcomes, like serum bilirubin, are popular in clinical research due to their relative ease of measurement, overreliance on them may result in misleading interpretation of trial results and inappropriate practice recommendations [30-32].…”
Section: Discussionsupporting
confidence: 53%
“…To be valid and applicable, and to inform policy and practice, RCTs need to assess effects on the outcomes of greatest importance to infants and their families and health services [28]. A recent study of nearly 2,000 RCTs showed a consistent increase in the proportion of trials reporting infant- and family-important outcomes over the past few decades [29]. Some areas of neonatal research, however, assess “surrogate,” rather than infant- and family-important, outcomes more commonly.…”
Section: Direct Relevance Of Evidence To the Target Populationmentioning
confidence: 99%